Near-surface Mounted Technology in Strengthening Reinforced Concrete Beam - Dazulhisham, Muhammad Adam Syahmi; Abdul Halim, Muhammad Arif Ikmal; Goh, Lyn Dee (International Journal of Sustainable Construction Engineering and Technology, 2024)
Structural strengthening is essential in civil engineering to ensure the integrity, safety, and longevity of various types of structures. Effective strengthening is required to solve these issues and lengthen the service life of structures as they naturally deteriorate with time. Hence, the use of various strengthening techniques to enhance the structural integrity of existing structures and infrastructure has gained prominence in recent years. This study demonstrates how Reinforced Concrete (RC) structures may benefit from Near-Surface Mounted (NSM) technology. The demonstration involves the experimental study on the performance of three different types of RC beams; unstrengthened RC beam, RC beam strengthened with NSM procedure using a conventional steel ribbed bar, and RC beam strengthened with NSM procedure using an iron-based smart memory alloy (Fe-SMA) ribbed bar. Consequently, three RC beams were evaluated at room temperature throughout the experimental testing, while the remaining three RC beams were examined after being exposed to a 200? temperature exposure. The experimental findings suggested that the performance of RC beams strengthened using NSM techniques was superior to that of RC beams that had not been strengthened. Although the results generally indicated a decrease in ultimate load obtained in the RC beams exposed to elevated temperature compared to RC beams tested at room temperature. However, the RC beams strengthened with an iron-based smart memory alloy ribbed bar recorded an increase in load-carrying capacity. These results demonstrate the substantial variations in load-bearing capacities among the beams and emphasise the efficiency of the strengthening application for RC beams in the constructions industry, particularly the use of iron-based smart memory alloy ribbed bars as strengthening materials